The Influence Of Counter Quality And Price On Tenant Loyalty At Terminal 3 Soekarno Hatta International Airport - Sabrina Rahma Putri; Winarto - Winarto; Fatchun - Hasyim (Politeknik Negeri Semarang, 2020)
Nowadays airport is not only a place where the aircraft take off and land, moreover airport defined as the enterprise. Soekarno-Hatta International airport is the largest airport in Indonesia which managed by PT Angkasa Pura II as the customer-oriented company that provides service product. This research aims to analyze the effect of counter quality and price on tenant loyalty. The research was conducted at terminal 3 Soekarno Hatta International Airport with all of tenants who rent the counter to PT Angkasa Pura II as the population. Data were collected by using the questionnaire with 52 respondents. This research used a multiple linear regression analysis. The results of this research shows that counter quality and price have significant and partially gives positive impact on tenant loyalty. Furthermore, counter quality and price simultaneously influenced Tenant Loyalty. The contribution of counter quality and price on tenant loyalty is 78.4%.